KONTRIBUSI PERIKANAN TERHADAP KEAMANAN PANGAN GLOBAL DAN LOKAL: KAJIAN DIVERSIFIKASI SUMBER PANGAN LAUT UNTUK KETERSEDIAAN PROTEIN BERKELANJUTAN - Rita Hayati; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
Global food security issues are becoming increasingly important as the world's population grows, consumption patterns change, and pressure on land-based food sources increases. In this context, fisheries play a strategic role as a major provider of high-quality animal protein that is relatively efficient, nutritious, and sustainable. This study aims to analyse the contribution of fisheries to food security, both on a global and local scale, and to examine the potential for diversifying marine food sources in supporting sustainable protein availability. The method used is a qualitative-descriptive approach through literature analysis and secondary data from international and national institutions. The results of the study show that the fisheries sector plays an important role not only in providing nutrition, but also in supporting the coastal economy, creating jobs, and strengthening socio-cultural identity. However, this strategic role faces challenges in the form of overfishing, marine ecosystem degradation, and climate change that threaten sustainability. In addition, the study found that marine food diversification, through the development of commodities such as seaweed, shellfish, crustaceans, non-high-value fish, and microalgae, can be an important strategy to reduce dependence on commercial fish sources. Diversification not only broadens the spectrum of protein consumption and meets micronutrient needs, but also contributes to ecosystem stability, food crisis mitigation, and the development of an environmentally friendly marine bioeconomy. Therefore, strengthening sustainable traditional fisheries must be aligned with innovations in marine food diversification, supported by national policies, international collaboration, and increased consumer awareness. Through this approach, marine-based food systems can become an important foundation in ensuring the availability of healthy, diverse, and sustainable protein for future generations.